The ideological background of ancient Chinese clothing culture - Bin Zhang; Ping Yang (Trans/Form/Ação)
China has been known as a country of clothing since ancient times, and its clothing culture is dazzling. Any nation’s art and culture have their specific philosophical thought background. Behind the Chinese costume culture, it also contains the ancient Chinese people’s ideological connotation. Ancient Chinese society spanned five thousand years, the social trend of thought was constantly changing, and the clothing system was also constantly updated. Through the study of the ideological history background of ancient Chinese clothing culture, we can broaden the research angle of ancient Chinese philosophy and more comprehensively understand the traditional clothing culture.